Teleorthodontics: Where Are We Going? From Skepticism to the Clinical Applications of a New Medical Communication and Management System - Antonino Lo Giudice; Vincenzo Ronsivalle; Pietro Venezia; Rosalia Ragusa; Giuseppe Palazzo; Rosalia Leonardi; Antonio Lazzara (International Journal of Dentistry)
Teleorthodontics represents the orthodontic care system involving remote management of orthodontic treatment. Despite skepticism, there are several advantages of including teleorthodontics in the clinical orthodontic practice. In the present review, we discuss the lights and shadows of this new communication healthcare system and its applications in the field of orthodontics that is destined to change the future of our clinical practice. For this purpose, we have provided a point-to-point analysis based on data from the most valuable scientific evidence on this topic. The information and data discussed in the present paper were obtained from the most relevant studies evaluating the performance of teleorthodontics and remote monitoring systems in clinical practice.